Chronic lung injury and impaired pulmonary function in a mouse model of acid ceramidase deficiency - Yu, Fabian P S; Islam, Diana; Sikora, Jakub; Dworski, Shaalee; Gurka, Jiří; López-Vásquez, Lucía; Liu, Mingyao; Kuebler, Wolfgang M; Levade, Thierry; Zhang, Haibo; Medin, Jeffrey A (American journal of physiology. Lung cellular and molecular physiology, 2018)
Farber disease (FD) is a debilitating lysosomal storage disorder (LSD) caused by a deficiency of acid ceramidase (ACDase) activity due to mutations in the gene ASAH1. Patients with ACDase deficiency may develop a spectrum of clinical phenotypes. Severe cases of FD are frequently associated with neurological involvement, failure to thrive, and respiratory complications. Mice homozygous ( Asah1P361R/P361R) for an orthologous patient mutation in Asah1 recapitulate human FD. In this study, we show significant impairment in lung function, including low compliance and increased airway resistance in a mouse model of ACDase deficiency. Impaired lung mechanics in Farber mice resulted in decreased blood oxygenation and increased red blood cell production. Inflammatory cells were recruited to both perivascular and peribronchial areas of the lung. We observed large vacuolated foamy histiocytes that were full of storage material. An increase in vascular permeability led to protein leakage, edema, and impacted surfactant homeostasis in the lungs of Asah1P361R/P361R mice. Bronchial alveolar lavage fluid (BALF) extraction and analysis revealed accumulation of a highly turbid lipoprotein-like substance that was composed in part of surfactants, phospholipids, and ceramides. The phospholipid composition of BALF from Asah1P361R/P361R mice was severely altered, with an increase in both phosphatidylethanolamine (PE) and sphingomyelin (SM). Ceramides were also found at significantly higher levels in both BALF and lung tissue from Asah1P361R/P361R mice when compared with levels from wild-type animals. We demonstrate that a deficiency in ACDase leads to sphingolipid and phospholipid imbalance, chronic lung injury caused by significant inflammation, and increased vascular permeability, leading to impaired lung function.
Keywords: Disease Models, Animal; Ceramides; myši; Animals; myši knockoutované; respirační funkční testy; ceramidy; Mice, Knockout; Acid Ceramidase; Lung; Homozygote; modely nemocí na zvířatech; plíce; Phenotype; poškození plic; fenotyp; Phospholipids; Mice; zvířata; Bronchoalveolar Lavage Fluid; Respiratory Function Tests; bronchoalveolární lavážní tekutina; fosfolipidy; homozygot; kyselá ceramidasa; Lung Injury